2019
DOI: 10.1017/s0950268819001158
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effectiveness of vaccine programs in dog populations

Abstract: Dogs harbor numerous zoonotic pathogens, many of which are controlled through vaccination programs. The delivery of these programs can be difficult where resources are limited. We developed a dynamic model to estimate vaccination coverage and cost-per-dog vaccinated. The model considers the main factors that affect vaccination programs: dog demographics, effectiveness of strategies, efficacy of interventions and cost. The model was evaluated on data from 18 vaccination programs representing eight countries. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…To this end, the concept of oral rabies vaccination (ORV) of dogs has gained renewed interest [ 7 , 8 , 9 , 10 , 11 ]. The added value of ORV of dogs as a complementary tool to mass parenteral dog vaccination campaigns has both quantitative and qualitative considerations; not only does it increase the overall vaccination coverage in the dog population, it specifically targets the free-roaming dog population [ 7 , 12 , 13 ]. In many areas, the majority of free-roaming dogs cannot be restrained and vaccinated by the parenteral route without special effort and are, therefore, considered inaccessible for rabies vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the concept of oral rabies vaccination (ORV) of dogs has gained renewed interest [ 7 , 8 , 9 , 10 , 11 ]. The added value of ORV of dogs as a complementary tool to mass parenteral dog vaccination campaigns has both quantitative and qualitative considerations; not only does it increase the overall vaccination coverage in the dog population, it specifically targets the free-roaming dog population [ 7 , 12 , 13 ]. In many areas, the majority of free-roaming dogs cannot be restrained and vaccinated by the parenteral route without special effort and are, therefore, considered inaccessible for rabies vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…In most rabies ontrol programs, a positive association exists between dog accessibility and efficiency of vaccinations delivered, as well as cost-effectiveness, predicated on parenteral vaccination. With ORV, this fundamental relationship can change (46). Several studies have shown that in areas with low dog accessibility, parenteral vaccination was either ineffective or inefficient, but ORV was able to achieve adequate coverage while remaining a cost-effective public health intervention (42,(45)(46)(47)(48).…”
Section: Rationale For the Consideration Of Oral Vaccines For Dog Vacmentioning
confidence: 99%
“…With ORV, this fundamental relationship can change (46). Several studies have shown that in areas with low dog accessibility, parenteral vaccination was either ineffective or inefficient, but ORV was able to achieve adequate coverage while remaining a cost-effective public health intervention (42,(45)(46)(47)(48). Although ORV has been used for >40 years in highincome countries to successfully control and eliminate rabies in wildlife (24,27), hesitancy to implement ORV as a component of mass dog vaccination campaigns has resulted in a dearth of evidence to argue for the integration, impact, and cost of these vaccines in the context of dog rabies control.…”
Section: Rationale For the Consideration Of Oral Vaccines For Dog Vacmentioning
confidence: 99%
See 2 more Smart Citations